2016
DOI: 10.3168/jds.2015-9795
|View full text |Cite
|
Sign up to set email alerts
|

Studying the relationship between on-farm environmental conditions and local meteorological station data during the summer

Abstract: High ambient heat and humidity have profound effects on the production, health, profitability, and welfare of dairy cattle. To describe the relationship between summer temperature and relative humidity in the barn and determine the appropriateness of using meteorological station data as a surrogate for on-farm environmental monitoring, a study was conducted on 48 farms in Ontario, Canada, over the summer (May through September) of 2013. Within-barn environmental conditions were recorded using remote data logge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 31 publications
5
23
0
Order By: Relevance
“…(2016) reported a standard of THI ≥ 68 for a heat stress day by calculating National Oceanic and Atmospheric Administration data for each state of the USA. However, due to the distances between the weather stations and farm, significant differences can occur between daily THI recorded in the cow barn and data from the nearest weather station (Shock et al ., 2016). Therefore, other physiological factors like rectal or vaginal temperatures, respiration rate, panting, sweating, feed intake, standing time and activity are often used to assess heat stress (West, 2003; Schutz et al ., 2008; Hansen, 2013).…”
mentioning
confidence: 99%
“…(2016) reported a standard of THI ≥ 68 for a heat stress day by calculating National Oceanic and Atmospheric Administration data for each state of the USA. However, due to the distances between the weather stations and farm, significant differences can occur between daily THI recorded in the cow barn and data from the nearest weather station (Shock et al ., 2016). Therefore, other physiological factors like rectal or vaginal temperatures, respiration rate, panting, sweating, feed intake, standing time and activity are often used to assess heat stress (West, 2003; Schutz et al ., 2008; Hansen, 2013).…”
mentioning
confidence: 99%
“…Variable frequency of clinical observation could have affected the results had the disease duration been shorter than the follow-up interval (2 to 3 d), but our frequent observations likely reduced the chance of missing signs of disease. Another limitation of our study was sensor failure for the macroenvironment data; such failures have been reported previously (Shock et al, 2016). Sensor failures could have been avoided by use of multiple sensors at each location, more frequent data downloads, and regular replacing of sensors.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, such environmental data should be used with the awareness that they might be discrepant from what a calf experiences at the hutch level. Indeed, a different study found significant differences between on-farm environmental conditions from data loggers placed in adult cow pens, including freestalls and tiestalls, and local weather stations (Shock et al, 2016). Weather station mean relative humidity daily summary values were not as well correlated with NOAA daily mean humidity, which might imply humidity is more location-specific and can be influenced by other environmental factors, such as flush systems beneath hutches or standing water in the calf hutch area.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The influence of the environment can not be ignored, as it can cause stress and thus negatively affect the condition of the organism (Fraser and Broom, 1990;Šoch et al 2000, 2005. High ambient heat and humidity have profound effects on the production, health, profitability, and welfare of dairy cattle (Shock et al, 2016). By altering the thermal environment for livestock, climate change could affect the costs and returns of animal production -thereby affecting the animal health, reproduction, and the efficiency with which livestock convert feed into retained products (especially meat and milk).…”
mentioning
confidence: 99%